Effects of dietary supplementation with a thymol-carvacrol blend on growth performance and intestinal health of poultry - Liu, Xiaoxia; Li, Xiang; Chen, Ruiying; Liu, Jing; Liu, Rui; Zhao, Ruting; Luo, Aiguo; Zhao, Jia; Hao, Jianwei; Yang, Shuming; Chen, Ailiang (Frontiers in Veterinary Science, 2026)
BackgroundAntibiotic resistance has intensified the search for alternatives in poultry production. Essential oils (EOs), particularly blends of carvacrol and thymol, have shown potential as natural growth promoters and antimicrobials. This study evaluated a composite carvacrol-thymol EO as an antibiotic substitute in broiler production, focusing on growth performance, serum biochemistry, intestinal morphology, and gut microbiota.Materials and methodsA total of 672 Aibayi-Yijia broilers were randomly assigned to seven treatment groups: control (CK), EO1 (200 g/t feed), EO2 (600 g/t feed), EO3 (1200 g/t feed), EO1+AG (EO 200 g/t + FON 0.15 g/kg feed), EO3+AG (EO 1200 g/t + FON 0.15 g/kg feed), and AG (FON 0.15 g/kg feed). Growth performance, serum biochemistry (TP, ALB, GLB, GLU, AST, GGT, CHOL, TG, IL), jejunal histology (villus height, crypt depth, V:C ratio), and cecal microbiota (16S rRNA sequencing) were assessed.ResultsSupplementation with EO (600 g/t) or florfenicol followed by 1200 g/t EO significantly increased ABW and ADFI (p < 0.05). EO (200 g/t or 1200 g/t) supplementation after antibiotics reduced serum TP, ALB, GLB, and CHOL (p < 0.05). Histological analysis showed increased villus height and V:C ratios with 1200 g/t EO. Cecal microbiota shifted, with increased Bacteroidetes and decreased Firmicutes.DiscussionThe composite carvacrol-thymol EO blend showed promise as an antibiotic alternative, improving growth performance, supporting intestinal health, and modulating the gut microbiota. Further research is needed to optimize dosing, assess long-term safety, and explore EO interactions for scalable use.